Identification of Factors Important for the Development of Family Businesses Using PESTLE - Olech, Igor; Olech, Artur; Wychowanek, Jacek (Identyfikacja czynników istotnych dla rozwoju firm rodzinnych z zastosowaniem PESTLE, 2025)
Aim: The purpose of this paper was to identify key factors affecting the operation of family businesses using the PESTLE method. Methodology: The PESTLE method allowing the identification of factors important for the functioning of family businesses was used. Results: The key factors for the operation and development of family businesses, indicated in the source literature, were identified, divided into political, economic, social, technological, legal and environmental factors. Implications and recommendations: The important problems for the development of family businesses include the issues of succession and intergenerational value transfer, the need to adapt to turbulent economic and technological conditions, as well as the changing legal determinants. The following recommendations arose from the study: the need to implement programmes to support succession in family businesses, to facilitate innovation and implementation of new technologies through, among others, increased access to funding, and to adapt legislation to the specificity of family businesses (regarding succession, protection of property rights), promotion of activities related to social responsibility and sustainable development. Originality/value: The identification of key determinants (political, economic, social, technological, legal and environmental) affecting the operation of family businesses.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 3, s. 104-118